Optimalisasi Pijat Bayi dalam Mengatasi Gangguan Tidur pada Bayi Usia 1 Bulan - Dessy Hidayati Fajrin; Cici Wahyuni (Ovary Midwifery Journal, 2023)
The World Health Organization (WHO) states that 33% of infants face sleep problems. In Indonesia, there are quite a lot of infants who experience sleep problems, which is around 55.2% of infants experience sleep disorders such as frequent waking at night so that sleep needs are not fulfilled. However, more than 72% of parents consider sleep disorders in infants not a problem or only a minor problem. Disruption of infant sleep patterns can be influenced by several factors such as diseases that cause infant discomfort, namely pain, emotional stress such as anxiety, noisy environments, fatigue caused by play, food and calorie intake. Scientifically, massage stimulates hormones in the body, a substance that regulates functions such as appetite, sleep, memory and learning, temperature regulation, mood, behavior, blood vessel function, muscle contraction, endocrine system regulation (regulation of metabolism, growth, and puberty) and depression. Infant massage can also increase the baby's weight, help babies who cannot sleep well, lack of appetite, and lack of concentration. This study uses qualitative research methods in the form of case studies by conducting a Varney management midwifery care approach. The research subject used one respondent with midwifery diagnosis Baby A aged 1 month with insufficient sleep. The study was conducted for 7 days by providing complementary infant massage care. The results of this study indicate that the number of hours baby A sleeps before being given a baby massage for 7 days is 12 hours / day, after being given a 20-minute baby massage for 7 days to 16 hours. It can be concluded that Holistic Physiological Midwifery Care for Infants and Toddlers by applying Evidence Based Midwifery Infant Massage can overcome sleep disorders in infants so that the baby's sleep needs are fulfilled.